(untitled) (Journal of Human Sciences, 2020)
Libya gained its independence by a United Nation Resolution and was lacked many basic things. The people that are reliable in building the country were economically, culturally poor and was exhausted by corrupt Turkish administrations and then by the Italian occupation. Accordingly, the government has recruited staff from abroad for the administrative affairs. When the legalization movement began in Libya, it used the help of Egyptian jurists because Egypt had benefited early from the western experience since the reign of Mohammed Ali pasha and his successors. Egyptian jurists transferred most of Egypt’s laws to Libya including the law of antiquities protection, issued in 1953, which some of its texts were quoted from the Egyptian law of 1951. In 1968, another antiquities law was passed; in this law, some terms have been changed in order to be in line with the modern state’s trend to unite the country under the leadership of a single federal government.